(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
This article discusses the problems and solutions encountered in the training of pre-service training, in which the aim is to instill in our youth a spirit of patriotism and correctly convey to them that it is honorable to fulfill their duty, and to prepare them to overcome the difficulties encountered.